Hierarchical Tori Connected Mesh Network - Rahman, M.M. Hafizur; Shah, Asadullah; Fukushi, Masaru; Inoguchi, Yasushi (Springer-Verlag Berlin Heidelberg, 2013)
Hierarchical interconnection networks provide high performance at low cost by exploring the locality that exists in the communication patterns of massively parallel computers. A Hierarchical Tori connected Mesh Network (HTM) is a 2D-torus network of multiple basic modules, in which the basic modules are 3D-mesh networks that are hierarchically interconnected for higher-level networks. This paper addresses the architectural details of the HTM and explores aspects such as degree, diameter, cost, average distance, arc connectivity, bisection width, and wiring complexity. We also present a deadlock-free routing algorithm for the HTM using two virtual channels and evaluate the network’s dynamic communication performance using the proposed routing algorithm under uniform traffic and bit-flip traffic patterns. We evaluate the dynamic communication performance of HTM, H3DM, mesh, and torus networks by computer simulation. It is shown that the HTM possesses several attractive features, including constant node degree, small diameter, low cost, small average distance, moderate (neither too low, nor too high) bisection width, small wiring complexity, and high throughput per link and very low zero load latency, which provide better dynamic communication performance than that of H3DM, mesh, and torus networks.